Social Media Analysis for Effective Information Dissemination and Promotions Using TOPSIS - Latifah Nurhasanah, Reka Hani; Anshor, Abdul Halim; Muhidin, Asep (Journal of Applied Informatics and Computing, 2024)
Social media has become an essential tool for spreading news and promotions. This research aims to evaluate the effectiveness of using social media as a strategy for disseminating information and promoting products using the TOPSIS method. Initial data was collected from a survey of social media users. The data was gathered through questionnaires distributed to various groups, including students, entrepreneurs, and office workers. The TOPSIS method was used to analyze the data and identify the most effective social media channels for information dissemination and promotion. The findings indicate that Facebook is the most effective platform for disseminating information, followed by Instagram and Twitter. Conversely, Instagram is the most effective platform for content promotion, followed by Facebook and YouTube. This study has significant implications for businesses and organizations that use social media for information dissemination and promotions. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method was used to evaluate and rank platforms based on criteria such as reach, accessibility, topicality, ease of use, creativity, informativeness, adaptability, transactionability, and security. The results show that TikTok is the best social media platform with the highest preference score of 0.755, followed by Facebook in second place, Instagram in third place, Twitter in fourth place, Telegram in fifth place, and YouTube in sixth place.